2017
DOI: 10.1177/1753495x17701847
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe meningioma mimicking preeclampsia: A case study

Abstract: We report a case of a left frontal lobe meningioma presenting in a woman with proteinuric preeclampsia in her first term pregnancy. The patient had a background of antepartum migraines that resolved in the second trimester of pregnancy. Postpartum, she required urgent surgery and sustained convulsions after surgery. She had no residual disease and has had another successful pregnancy. This case highlights the importance of cerebral imaging in the context of an atypical clinical course of preeclampsia. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is well-established that headaches, nausea, visual disturbances, and focal deficits, are signs of intracranial tumors or lesions. 1,15 But initial symptoms such as headache, nausea as in our case could be subtle, or even could be attributed to other conditions and may warrant a heightened sense of awareness on the part of the clinician. A review of the literature also revealed a patient with meningioma who initially presented with nausea and severe headaches, which were initially attributed to preeclampsia.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It is well-established that headaches, nausea, visual disturbances, and focal deficits, are signs of intracranial tumors or lesions. 1,15 But initial symptoms such as headache, nausea as in our case could be subtle, or even could be attributed to other conditions and may warrant a heightened sense of awareness on the part of the clinician. A review of the literature also revealed a patient with meningioma who initially presented with nausea and severe headaches, which were initially attributed to preeclampsia.…”
Section: Discussionmentioning
confidence: 76%
“…A review of the literature also revealed a patient with meningioma who initially presented with nausea and severe headaches, which were initially attributed to preeclampsia. 15 Our patient had occasional nausea and headaches, which could have justified a neuroimaging study, but it was not performed. These somatic symptoms can be associated with depression and thus can be misleading.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation